2019
DOI: 10.1167/tvst.8.5.32
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Macular Edema: The Effect of IL-6 and IL-6R Blockade on Human Blood–Retinal Barrier Integrity In Vitro

Abstract: PurposeMacular edema (ME) is a leading cause of visual loss in a range of retinal diseases and despite the use of antivascular endothelial growth factor (anti-VEGF) agents, its successful treatment remains a major clinical challenge. Based on the indirect clinical evidence that interleukin-6 (IL-6) is a key additional candidate mediator of ME, we interrogated the effect of IL-6 on blood–retinal barrier (BRB) integrity in vitro.MethodsHuman retinal pigment epithelial cell (ARPE-19) and human retinal microvascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Moreover, considering the role of histamine as a neurotransmitter, 44 it seems reasonable that brain and retinal endothelial cells should be able to maintain their vascular integrity in the presence of histamine. Other reports have noted that HRMEC do increase permeability similarly to other endothelial cell types in response to some factors, such as VEGF, but are unresponsive to others, such as IL‐6 45‐47 . Hence, the distinct responses to histamine of HRMEC, compared to endothelial cells from other vascular beds, provides further evidence for the heterogeneity of vascular endothelial cells from different tissues 48 …”
Section: Discussionmentioning
confidence: 92%
“…Moreover, considering the role of histamine as a neurotransmitter, 44 it seems reasonable that brain and retinal endothelial cells should be able to maintain their vascular integrity in the presence of histamine. Other reports have noted that HRMEC do increase permeability similarly to other endothelial cell types in response to some factors, such as VEGF, but are unresponsive to others, such as IL‐6 45‐47 . Hence, the distinct responses to histamine of HRMEC, compared to endothelial cells from other vascular beds, provides further evidence for the heterogeneity of vascular endothelial cells from different tissues 48 …”
Section: Discussionmentioning
confidence: 92%
“…On closer examination, it was found that patients with MO secondary to CRVO or BRVO showed a higher IL-6 concentration than patients with CRVO or BRVO alone. Indeed, the administration of IL-6 disrupts the integrity of human retinal pigment epithelial cells (ARPE-19) leading to increased cellular permeability concomitant with a low trans endothelial electrical resistance (TEER) 260 . This indicates the potential use of IL-6 as a biomarker and therapeutic target of retinal vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Its levels have been shown to be increased in several number of other retinal diseases such as retinal vein occlusions and uveitic macular edema. In uveitic macular edema, systemic inhibition of IL-6 has shown benefits (Mesquida et al, 2019). However, an in vitro model has shown that IL-6 can lead to break down of the outer retinal blood brain barrier, but not of the inner blood-retinal brain barrier (Mesquida et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In uveitic macular edema, systemic inhibition of IL-6 has shown benefits (Mesquida et al, 2019). However, an in vitro model has shown that IL-6 can lead to break down of the outer retinal blood brain barrier, but not of the inner blood-retinal brain barrier (Mesquida et al, 2019). However, even though both barriers are affected in DME, the latter is the main one involved.…”
Section: Discussionmentioning
confidence: 99%